2021
DOI: 10.1111/nyas.14716
|View full text |Cite
|
Sign up to set email alerts
|

The roles of mitochondrial dynamics and NLRP3 inflammasomes in the pathogenesis of retinal light damage

Abstract: With the widespread popularity of electronic products and the diversification of lighting equipment, ocular photochemical damage caused by light has attracted research attention. Although such equipment mainly cause damage to the retina, the specific pathogenesis has not been systematically elucidated. Thus, the goal of this study was to explore the relationship between mitochondrial dysfunction and the activation of the NOD-like receptor protein 3 (NLRP3) inflammasome in retinal cell death caused by light dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The LCM imaging revealed that the enhanced mitochondrial aspect ratio in MSU crystal-treated BMDMs was also largely reversed by Drp1 knockdown ( Figure 2(b) ). Since the excessive mitochondrial fission mediated by Drp1 could exacerbate the production of mitochondrial ROS [ 28 ], we also observed that Drp1 knockdown significantly decreased mitochondrial ROS and total intracellular ROS generation in MSU crystal-treated BMDMs (Figures 2(c) and 2(d) ). We sought to explore whether Drp1 knockdown mediated antioxidant protein expression induced by MSU crystals.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The LCM imaging revealed that the enhanced mitochondrial aspect ratio in MSU crystal-treated BMDMs was also largely reversed by Drp1 knockdown ( Figure 2(b) ). Since the excessive mitochondrial fission mediated by Drp1 could exacerbate the production of mitochondrial ROS [ 28 ], we also observed that Drp1 knockdown significantly decreased mitochondrial ROS and total intracellular ROS generation in MSU crystal-treated BMDMs (Figures 2(c) and 2(d) ). We sought to explore whether Drp1 knockdown mediated antioxidant protein expression induced by MSU crystals.…”
Section: Resultssupporting
confidence: 53%
“…Mito/autophagy is also involved in MSU crystal-induced NLRP3 inflammasome activation or IL-1 β release [ 54 ]. Drp1-mediated excessive mitochondrial fission can promote the activation of the NLRP3 inflammasome [ 28 ]. However, the role of Drp1 signaling on NLRP3 inflammasome activation induced by MSU crystals is ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is deemed a precursor to cell death ( 79 ), and the core reason for heart failure progression ( 6 ). Among the many mechanisms that influence mitochondrial stability, mitochondrial dynamics is crucial to cell quality control and function ( 80 , 81 ) and its disturbance is one cause of apoptosis ( 82 ). For instance, mitochondrial fusion promotes structural and functional stability of the inner membrane, thus protecting cells from apoptosis, while fission is related to cell apoptosis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome activation was also observed in diabetic cognitive impairment model mice/rats [ 34 , 35 ]. Mitochondrial fission was reported to regulate NLRP3 inflammasome activation [ 36 38 ]. Further experiments in vitro revealed that when the ratio of p-Drp1S616/DRP1 was upregulation, the activation of NLRP3 inflammasomes, including NLRP3, cle-caspase-1, and IL-1 β was increased.…”
Section: Discussionmentioning
confidence: 99%